1998
DOI: 10.1007/bf03350321
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induces tyrosine dephosphorylation of a 92 kDa protein in suspended monocytes

Abstract: Monocytes bear insulin receptors similar to those expressed in other tissues, but insulin action in these cells remains unclear. There is evidence that adhesion, by generating a complex array of irreversible transformations, may modify the response of cells to other stimuli, such as hormones. The present study aimed to characterise the pattern of insulin induced tyrosine phosphorylation of monocytes in suspension. Monocytes in suspension were obtained by sequential gradient centrifugation and the tyrosine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The possibility that proteolytic enzymes could be IGFBP and tissue specific provides a potential mechanism of specific delivery of a fraction of circulating IGFs to certain target cells [10, 20]. Holly et al [21]have suggested that IGFBP-3 may serve as the main circulating carrier, forming a reservoir which can supply IGFs to the tissues. In the tissues, proteolysis of IGFBP-3 makes this IGF available to the target cell receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that proteolytic enzymes could be IGFBP and tissue specific provides a potential mechanism of specific delivery of a fraction of circulating IGFs to certain target cells [10, 20]. Holly et al [21]have suggested that IGFBP-3 may serve as the main circulating carrier, forming a reservoir which can supply IGFs to the tissues. In the tissues, proteolysis of IGFBP-3 makes this IGF available to the target cell receptors.…”
Section: Introductionmentioning
confidence: 99%